Beyond access: tailoring ODL provision to advance social justice and development - Makhanya, M; Mays, T; Ryan, P (South African Journal of Higher Education, 2016)
This paper observes that while open and distance learning (ODL) has demonstrably created greater opportunities for access to higher education opportunities, access alone is a necessary but insufficient criterion for advancing the twin causes of development and social justice. The article considers social justice and supporting learners in Open and Distance Learning (ODL), particularly in terms of what is taught and the ways in which teaching/ learning is mediated. It argues that the age, needs, and expectations of ODL learners, particularly in Africa, are changing and that these changes should be considered and addressed. The manuscript starts from an assumption that learning is a basic human activity, but observes that what is learned in higher education is both more systematic and more purposeful and therefore requires careful mediation. It considers the Unisa case, recognizing a shift towards an epistemology of social-constructivism, where progressive scaffolding allows the learner to move to more independent learning. The article then identifies some of the key assumptions that need to inform changed practice in order to produce a deeper sense of connection and relevance with learners: from appreciating that learning resides with the learner, through to redesigning the distance learning approach. The article sets out conceptual issues that should be of interest to those starting new ODL initiatives. It is basically a position paper for Unisa, but it seeks to manifest many of the root assumptions underlying its interpretation of ODL. As such it is hoped that the article will be of interest to international readers – especially those outside Africa – providing an African perspective on challenges faced by higher education more generally.